Effects of different levels of dietary black cumin (Nigella sativa L.) and fenugreek (Trigonella foenum-graecum L.) and their combination on productive traits, selected blood constituents, microbiota and immunity of broilers. Issue 5 (3rd October 2022) - Laudadio, Vito; Nasiri-Dehbaneh, Mohsen; Bilal, Rana Muhammad; Qotbi, Ali; Javandel, Faramin; Ebrahimi, Abbas; Seidavi, Alireza; Slozhenkina, Marina; Gorlov, Ivan; Dunne, Peter G.; Tufarelli, Vincenzo
Abstract: The effects of inclusion of powdered seeds of black cumin (B) ( Nigella sativa L.) and fenugreek (F) ( Trigonella foenum-graecum L.) on productive traits, selected blood constituents, microbiota and immunity of broilers were studied. A total of 648 day-old chicks were randomly assigned to nine treatments, with four pen replicates, each with 18 birds, including three levels of B seed powder (BSP; 0, 5 or 10 g/kg) and three levels of F seed powder (FSP; 0, 5 or 10 g/kg) in a 3 × 3 factorial arrangement. Neither powder affected feed intake. The FSP increased ( p  = 0.048) feed conversion ratio (FCR), but decreased daily BW gain ( p  = 0.02) between days 0 and 21, while BSP increased daily gain between days 22 and 42 and overall (both p  = 0.005). Abdominal fat was decreased ( p  = 0.003) by BSP. Blood constituents were unaffected by either powder, but ileal Escherichia coli were decreased ( p  = 0.039) at day 42. The BSP increased a range of immunological titers, where BSP affected positively the measured variables. The interactions between BSP and FSP, specifically on broiler carcass cuts, suggested that where BSP is included at 10 g/kg, the inclusion of FSP at the same level may provide no additional benefit. Thus, while either powder could be included separately, the co-inclusion of both at 10 g/kg is not recommended.